2021
DOI: 10.48550/arxiv.2109.01920
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Schrödinger-Poisson Solitons: Perturbation Theory

J. Luna Zagorac,
Isabel Sands,
Nikhil Padmanabhan
et al.

Abstract: Self-gravitating quantum matter may exist in a wide range of cosmological and astrophysical settings from the very early universe through to present-day boson stars. Such quantum matter arises in a number of different theories, including the Peccei-Quinn axion and UltraLight (ULDM) or Fuzzy (FDM) dark matter scenarios. We consider the dynamical evolution of perturbations to the spherically symmetric soliton, the ground state solution to the Schrödinger-Poisson system common to all these scenarios. We construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(53 reference statements)
1
4
0
Order By: Relevance
“…This gives time-averaged density profiles that agree reasonably well with the desired input profile. The density fluctuations in the soliton region resemble those found in full Schrödinger-Poisson simulations [26], in agreement with previous work that found that soliton fluctuations can be explained by wave interference between the lowest eigenmodes [22,23]. Our simulations find that including the soliton can enormously enhance heating of stellar orbits, depending on the soliton mass, in agreement with previous work [24].…”
Section: Simulationssupporting
confidence: 91%
See 2 more Smart Citations
“…This gives time-averaged density profiles that agree reasonably well with the desired input profile. The density fluctuations in the soliton region resemble those found in full Schrödinger-Poisson simulations [26], in agreement with previous work that found that soliton fluctuations can be explained by wave interference between the lowest eigenmodes [22,23]. Our simulations find that including the soliton can enormously enhance heating of stellar orbits, depending on the soliton mass, in agreement with previous work [24].…”
Section: Simulationssupporting
confidence: 91%
“…1 shows examples. This approach is accurate to first order in perturbation theory and neglects the nonlinear interactions between different modes, which should be sufficient for our calculations, although it may be worthwhile to study whether greater accuracy can be achieved by going to higher order in time-dependent perturbation theory [23].…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a post-merger halo, the central soliton may be far from its ground state, suggesting that these effects might be substantially enhanced in astrophysical settings, resulting in the outward diffusion of light objects residing in the center of the soliton [36]. In addition, the coupling and impulsive heating associated with a single SMBH-soliton interaction could be analyzed in detail using eigenstate expansions of the soliton potential [42], facilitating the semi-analytic treatment of these systems.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This opens the door to detailed investigations of wave halo substructure. Indeed, there are a few recent papers heading in this direction: Dalal et al [60] employed the method of Widrow and Kaiser to construct wave dark matter halos, for the purpose of studying the scattering of tidal streams by the interference substructure; we in [61] studied soliton random walk and oscillations by decomposing a wave dark matter halo into its eigenmodes; Zagorac et al [62] studied the distortions of solitons using perturbation theory.…”
Section: Introductionmentioning
confidence: 99%